2016
DOI: 10.1016/j.ijfatigue.2016.05.034
|View full text |Cite
|
Sign up to set email alerts
|

Very high cycle fatigue for single phase ductile materials: Comparison between α-iron, copper and α-brass polycrystals

Abstract: In this paper, the main results obtained in the framework of a National French Agency project called DISFAT, standing for ''Dissipation in Fatigue", are presented. The project was dedicated to the microplastic mechanisms leading to crack initiation in the case of ductile metals loaded in very high cycle fatigue. Fatigue tests were carried out at 20 kHz using an ultrasonic facility. In order to investigate the microplastic mechanisms, slip markings at the surface of the specimens were observed and the self-heat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
7
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 31 publications
3
7
0
Order By: Relevance
“…For instance, for the stress amplitude of 200 MPa, which is equal to 30 % of the ultimate stress amplitude, the dissipated energy per cycle is 800 J=m 3 =cycle. This is consistent with the results obtained by Favier et al for alpha-iron [14].…”
Section: Resultssupporting
confidence: 94%
See 2 more Smart Citations
“…For instance, for the stress amplitude of 200 MPa, which is equal to 30 % of the ultimate stress amplitude, the dissipated energy per cycle is 800 J=m 3 =cycle. This is consistent with the results obtained by Favier et al for alpha-iron [14].…”
Section: Resultssupporting
confidence: 94%
“…Therefore, for such high strain rates, the transition temperature for the DP600 should be higher than room temperature. As a result, and as suggested by Favier et al [14] for alphairon, the thermally activated mode, which is typical of a bcc structure, prevails at room temperature for a 20-kHz cyclic loading at low stress amplitudes. Therefore, the dissipated energy probably results from the to-and-fro motion of dislocations that result in slight changes in the material internal state and are consistent with Eqs 11 and 12.…”
Section: Resultssupporting
confidence: 76%
See 1 more Smart Citation
“…These research works can be categorized into two groups. The first category consists of studies that have used dissipation estimations to investigate the fatigue damage process and crack initiation mechanisms in very-high-cycle fatigue regimes [9][10][11][12][13][14][15][16]. For instance, Xue et al [11] and Wagner et al [12] used in situ thermography and fracture surface analysis for different steels and aluminum alloys under ultrasonic fatigue loading and showed that a correlation exists between the temperature fields in the specimen and the fatigue damage process.…”
Section: Introductionmentioning
confidence: 99%
“…In general, for both low-and high-frequency fatigue tests, the classical temperature evolution of a material that undergoes fatigue straining and damage up to failure consists of three main stages: the first stage is an initial increase at the beginning of the test, the second stage is associated with a steady-state or a slight increase and the last stage is a final sharp increase that is related to fracture initiation (see, for example, [13,16,20]). Ranc et al [20] observed that ferritic-pearlitic C45 steel that was loaded cyclically at 20 kHz did not follow this classical thermal response and exhibited a steep increase in temperature up to a few hundreds of degrees, which did not lead to a final rupture.…”
Section: Introductionmentioning
confidence: 99%